Cardiopulmonary exercise testing in Fontan patients: unmasking the secret of Super-Fontans. (3rd October 2022) - Paiva, M; Rato, J; Santos, R; Cunha, G; Gomes, D; Cordeiro, S; Madeira, S; Guerreiro, S; Moreno, L; Durazzo, A; Mendes, M
Abstract: Background: Exercise capacity is usually reduced in Fontan patients, however there is a subset of patients who have normal exercise capacity and better outcomes, the "Super-Fontans". The aim of this study was to characterize a cohort of Fontan patients undergoing cardiopulmonary exercise testing (CPET) and identify predictors of better functional capacity. Methods: Single center retrospective analysis of consecutive Fontan patients aged >10 years old who underwent CPET, between March 2018 and May 2021. Peak respiratory exchange ratio1.05 defined maximal CPET. Peak VO2 (pVO2) as a percentage of its predicted value was used as reference value to stratify patients in tertiles. Patients in 3rd tertile, with a percentage predicted pVO2 superior to 75%, were considered good-performers. Blood tests and transthoracic echocardiogram (TTE) were performed on the same day. Additional data were collected from electronic charts. Results: In total, 49 patients were included (mean age 19±7 years old, 67% male) with intra or extracardiac conduit implanted in mean 12±7 years prior to the CPET. The most common primary diagnoses were tricuspid/pulmonary atresia (43%), followed by unbalanced complete AV septal defect (14%) and double inlet left ventricle (14%). 12 patients had a systemic right ventricle. All, except 5 patients, had preserved systolic ventricular function and 37% had moderate to severe AV regurgitation. The majority had normal hemoglobin levels (median 15.6 g/dL), hepatic enzymes (median total bilirubin 0.8 mg/dL), renal function (median creatinine 0.8 mg/dL) and low NT-proBNP (median 122 pg/mL). All patients had maximal CPET, median %VO2 at VT1 was 57% of peak and mean pVO2 was 66±14% of the predicted. Most patients (69%) showed exercise limitation due to cardiovascular cause, followed by O2 desaturation, present in 22% of CPETs. The age of Fontan completion was not associated with functional capacity (p=0.6). The good-performer group comprised 13 patients (27%), all in sinus rhythm, of which 10 were physically active. Compared with the remainder, this group had higher VO2 at VT1 (18.7 vs. 14.6, p=0.01) and VO2 at VT2 (25.9 vs. 22.1, p=0.02), both in mL/kg/min. Also, peak heart rate (% predicted) (90 vs. 81, p=0.03) was higher in this subgroup – fig.1. Conversely, differences on TTE parameters (GLS and AV valve regurgitation) and blood biomarkers were not statistically significant. On multivariable analysis, no single variable predicted better functional capacity. Conclusion: In our Fontan cohort, most patients had reduced exercise capacity, largely due to cardiovascular dysfunction. However, "Super-Fontans" stood out as they had a higher anaerobic threshold illustrating their better physical condition. These findings highlight the role of regular physical activity in Fontan patients as a cornerstone for better functional capacity. Funding Acknowledgement: Type of funding sources: None.